Estimating velocity in Gasoline Direct Injection sprays using statistical pattern imaging velocimetry. (July 2019) - Sivathanu, Yudaya; Lim, Jongmook; Muliadi, Ariel; Nitulescu, Oana; Shieh, Tom
Statistical pattern imaging velocimetry (SPIV) is a new technique for the estimation of the planar velocity field from the high-speed videos. SPIV utilizes an ensemble of either backlit or side lit videos to obtain full planar velocities in sprays and flames. Unlike conventional particle imaging velocimetry, statistical pattern imaging velocimetry does not require well-resolved images of particles within turbulent flows. Instead, the technique relies of patterns formed by coherent structures in the flow. Therefore, SPIV is well suited for the estimating planar velocities in sprays and turbulent flames, both of which have well-defined patterns embedded in the flow videos. The implementation of the SPIV technique is relatively quite straightforward since high-speed videos can be readily obtained either in a laboratory or production floor setting. The biggest challenge for the SPIV techniques is that the procedure is computationally expensive even with an ordinary mega-pixel camera. To improve the computation speed, a successive partitioning scheme was employed. In addition, to improve spatial resolution to subpixel dimensions, a weighted central averaging scheme was used. With these two enhancements, the SPIV method was used to obtain planar radial and axial velocities in a spray emanating from a GDI injector. Sprays from GDI injectors are very dense (with obscuration levels close to the injector being greater than 99%), and velocity measurements are difficult. However, further away from the nozzle, a Phase Doppler Anemometer can be used to obtain velocity measurements. The velocities obtained using these two methods showed reasonable agreement.